TRADE DYNAMICS: EXPLORING FUTURE DIRECTIONS OF CHINA-RUSSIA COOPERATION - Vokhidova M.Kh.; Urokova D.A. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
The purpose of this article is to explore the potential directions of foreign trade cooperation between China and Russia, delving into how this dynamic relationship could evolve in the coming years. Also, this article analyzes the main directions of the economic cooperation of the countries. Given the current state of robust growth and strategic alignment in their trade relations, it's important to consider the future pathways and opportunities that could further enhance and diversify this economic partnership.